Gyank [detail]. - DerVartanian, Michelle Coco. (Tufts Archival Research Center, 2019)
Installation view from Liminal Space: 2019 SMFA Senior Thesis Exhibition. Thesis project statement: I create work that is exclusively auto-biographical. I find that the work I create about myself and my experiences best reflects my lighthearted point of view and dark sense of humor. Art is a therapeutic process for myself and I incorporate my use of witty remarks and banter in my imagery to accurately depict my personal ways of coping.